Efektivitas Penerapan Model Pembelajaran Group Investigation Terhadap Keterampilan Proses Sains pada Siswa Kelas VIII SMP Negeri 17 Halmahera Selatan - Muhtar, Ernawati (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research aims to find out whether the group learning model is implemented Investigation is effective in improving the science process skills of students at SMP Negeri 17 South Halmahera. The type of research is quantitative with experimental methods, one-group pre test post test design research design. The sample in this research was 28 class VIII students of SMP Negeri 17 South Halmahera, obtained using the Simple Random Side technique and seen from the table determining the number of samples from a certain population, with an error rate of 5%. The data obtained from the research sample was in the form of students' science process skill scores regarding growth and development in living things. Data analysis was carried out using paired sample t-test. The results of research data analysis show that the application of the Group Investigation learning model is effective on the science process skills of students at SMP Negeri 17 South Halmahera. This is proven by the average results of the analysis of science process skills obtained from observation sheets of 81.96 and the average results of post-test data analysis of 82.35. Proven by hypothesis testing using paired sample t-test sig value. (2-tailed) is 0.000 < 0.05, so H0 is rejected and H1 is accepted.